A river-dominated to tide-dominated delta transition: A depositional system case study in the Orinoco heavy oil belt, Eastern Venezuelan Basin. (August 2020) - Huang, Wensong; Li, Shengli; Chen, Heping; Fu, Chao
Abstract: The Orinoco heavy oil belt (OHOB), which has the most significant heavy oil reserve in the world, has shown various sedimentary patterns and different evolution processes within its different blocks. We selected two blocks, Junin in the west and Carabobo in the east, to analyze the depositional environment distinctions due to different transgression processes. Based on the interpretation of 3D seismic data and electrical well-logging facies and analysis of depositional phenomena using cores, we clarified diverse depositional associations and constructed a sedimentary evolution model of the depositional system in the study area. We suggest that the depositional system transitioned from a braided river delta to a tide-dominated delta in the Early Miocene and that two factors mainly controlled the transition: paleo-flow and paleo-geomorphology, which are related to tectonic uplift and transgression processes. Transgression increased gradually through tectonic activity, though transgression rates varied area to area, resulting in different depositional environment transitions and sand-body distribution patterns. In the Carabobo block (east), a gentle slope developed, indicating a fast transgression rate. The intense interaction between river and tide flow led to a large inter-distributary channel area with high-sinuosity- or tidal-channels (relative to the Junin block). In the Junin block (west), tectonic activity developed a large accommodation area providing space for the sediment produced, slowing the transgression rate, and contributing to a mainly fluvial delta environment. Due to the gradual intensive transgression, channel stack patterns transitioned from braided-to meandering-channel in the river dominated delta or tidal-channel in the tide-dominated delta. Highlights: Depositional environment analysis in the Orinoco heavy oil belt. Braided river delta to tide-dominated delta transition in the early Miocene. Fast and slow transgression in the east (Carabobo) and west (Junin), respectively. Channel stack patterns transitioned from braided-to meandering- or tidal-channel.